PENGARUH GEOMETRIK JALAN TERHADAP TINGKAT KECELAKAAN LALU LINTAS BANJAR PATROMAN – PANGANDARAN (BANDUNG KM 150 + 000 - KM 151 + 000) - Pebriana, Rian; Saepudin, Uu; Defiana, Yanti (Jurnal Ilmiah Teknik Sipil, 2026)
his study is entitled "The Influence of Road Geometries on the Traffic Accident Rate on the Banjar Patroman– Pangandaran Road (Km Bandung 150+000 – Km 151+000)." The purpose of this study is to determine the extent to which road geometric conditions, particularly horizontal alignment, influence the traffic accident rate on this road section. The research method used is quantitative descriptive analysis with a case study approach. The data used include traffic accident data from 2020–2024, traffic volume data, and road geometric data consisting of curve radius, degree of curvature, and sight distance. Accident rates were analyzed using the Equivalent Accident Number (EAN) and Accident Rate (AR) methods, while road capacity was analyzed using the Indonesian Road Capacity Manual (PKJI, 2023). The relationship between geometric factors and accident rates was tested using linear regression analysis. The results of the study indicate that the Banjar Patroman–Pangandaran road section (Km Bandung 150+000 – Km 151+000) is included in the category of accident-prone areas (black spots) with an EAN value higher than the critical limit. The geometric factors that most influence the accident rate are the curve radius (R) and the degree of curvature (D), where the smaller the R value and the larger the D value, the higher the potential for accidents. In addition, the availability of stopping sight distance (Jh) also has a significant relationship with the number of accidents. The conclusion of this study is that the geometric conditions of the road that do not meet standards contribute significantly to the high number of accidents on the Banjar Patroman–Pangandaran road section. Therefore, efforts are needed to improve the geometric design, especially on the curves and sight distance, in order to create a safer and more comfortable road for users.